(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This study examines the thematic diversity and artistic mastery of one of the major figures of Persian-Tajik literature, Hafez Shirazi. His ghazals encompass themes such as love, divine passion, Sufi ideas, and the transience of life. The analysis focuses on the poet’s skill in crafting imagery, his use of wordplay, metaphor, allegory, and simile. Additionally, it highlights his unique stylistic approach within the ghazal genre and his significant contribution to classical poetry.